MACE-AL - Rehbein, Ines; Ruppenhofer, Josef; Steen, Julius (Universität, 2020)
A method for detecting noise in automatically annotated sequence-labelled data, combining MACE (Hovy et al. 2013) with Active Learning.
Production date: 2017
Kind of data: Python code
Gesehen am 31.03.2020
Keywords: Forschungsdaten; Datenbank